Protocol for Guo’s aortIc Arch recoNstrucTion: a prospective, multicentre and single-arm study to evaluate the safety and efficacy of the WeFlow-Arch modular inner branch stent-graft system for aortic arch lesions (GIANT study) - Lijun Wang; Wei Guo; Feng Liu; Dan Rong; Yangyang Ge; Hongpeng Zhang; Xin Jia; Xiaohui Ma; Jiang Xiong; Tingting Fan (BMJ Open, 2022)
Introduction Endovascular repair of the entire aortic arch provides treatment opportunities for patients with aortic arch lesions who are intolerant to open surgery. However, the complex anatomical configuration, high-speed blood flow and long access from the femoral artery increase the difficulty of endovascular aortic arch repair. On the basis of our earlier studies, a new modular inner branch stent-graft system was developed specifically for lesions located in the aortic arch and part of the ascending aorta. This study aims to evaluate the safety and efficacy of the novel modular branch stent-graft system in patients with aortic arch lesions who are unsuitable for open aortic arch replacement.Methods and analysis This prospective, multicentre, single-arm, clinical trial will enrol 80 patients with aortic arch lesions requiring intervention, namely, true aortic arch aneurysms, pseudo-aortic arch aneurysms and penetrating ulcers involving the aortic arch. Clinical information and CT angiography (CTA) images will be collected and analysed to investigate the safety and efficacy of the novel modular branch stent-graft system. Patients will be followed up for 5 years. The primary outcome will be all-cause mortality and severe stroke within 12 months after the procedure. In addition, this trial will evaluate mid-term to long-term clinical and imaging outcomes through the annual clinical and CTA follow-up for 2–5 years postoperatively.Ethics and dissemination We have registered the study on a registry website (https://clinicaltrials.gov/ct2/home). The study findings will be disseminated through peer-reviewed journals, physician newsletters, conferences and the mass media.Trial registration number NCT04765592.